Implementation of Class XI Culinary Students of Nusatama Padang Vocational School Regarding Sanitation, Hygiene, and Occupational Health and Safety During Oriental Food Practices - Elda Febri Dollah; Cici Andriani; Elida Elida; Juliana Siregar (Universitas Negeri Padang, 2025)
This study aims to describe the implementation of sanitation, hygiene, and occupational health and safety (K3) by class XI Culinary students of SMK Nusatama Padang in the practice of oriental food subjects. This study uses a qualitative approach with descriptive methods. The subjects of the study were class XI Culinary students and productive teachers who teach the subject. Data collection techniques were carried out through observation, interviews, and documentation. The results of the study indicate that students' understanding of sanitation, hygiene, and K3 is quite good, but their implementation is not consistent. In the aspect of personal hygiene, students have not fully implemented personal hygiene standards, such as washing hands properly and using practical attributes according to procedures. In the aspect of kitchen hygiene, some students have maintained the cleanliness of the kitchen and equipment, but there are still negligence, especially in handling waste and storing food ingredients. As for the aspect of occupational safety (K3), students have known and used personal protective equipment (PPE), but are still often negligent in its application, and supporting facilities such as a first aid kit are not yet available in the practical kitchen. It can be concluded that although students' understanding is quite good, supervision and habituation of hygienic and safe behavior still need to be improved to comply with culinary industry standards.